THE EFFECT OF TAX INCENTIVES AND SERVICE QUALITY ON MOTOR VEHICLE TAXPAYER COMPLIANCE WITH TAX SYSTEM DIGITALIZATION AS A MODERATING VARIABLE - Tri Alisba, Isnadia; Maelani, Puspita; Handayani, Novi; Samsinar, Ade (Income, 2025)
Motor vehicle taxpayer compliance plays a crucial role in increasing regional tax revenue. In Serang City, compliance remains low, with services and tax system digitization suboptimal. Despite the provision of e-Samsat services and tax deductions, compliance has not been maximized, necessitating investigation into the influencing factors. This study aims to determine the effect of tax incentives and service quality on motor vehicle taxpayer compliance in Serang City, and to examine the role of tax system digitization as a moderating variable in Serang City. The method used in this study is a quantitative approach with data collection techniques through the distribution of questionnaires to 72 motor vehicle taxpayer respondents who make payments at the Serang City Samsat Office. Data were analyzed using multiple linear regression and interaction tests (moderated regression analysis) with the help of SPSS. The results show that tax incentives and service quality have a positive and significant effect on taxpayer compliance. Tax system digitization has been shown to moderate the effect of tax incentives on taxpayer compliance, but not the effect of service quality. The conclusion of this study is that the provision of tax incentives and service quality are effective in increasing compliance. However, successful digitalization requires increased digital literacy and better system infrastructure.